Iklim Organisasi yang Dialami Perawat Selama di Rumah Sakit - Gadis Halizasia; Siti Saidah Nasution (Journal of Telenursing (JOTING), 2023)
This study aims to examine changes in the organizational climate of nurses in hospitals. The method used is a systematic review based on Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). The database used in this research is Science Direct, Proquest, PubMed, Garuda Portal, PPNI Journal, and Google Scholar articles published from 2014-2022. The study results indicate a change in an organizational climate closely related to the performance of nurses in the hospital. In conclusion, it shows an organizational environment that influences nurses when working in hospitals and influences the psychological nature of nurses while working. In conclusion, the better the corporate environment applied in the hospital, the better the quality of service so that nurses carry out their work with full responsibility and feel satisfied and motivated with their work. Keywords: Organizational Climate, Nurses